Keragaan Hasil Jarak Pagar (Jatropha curcas L.) pada Berbagai Umur Pemangkasan Yield of Jatropha curcas L. at Different Pruning Time - Bambang Budi Santoso (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
Seed and oil production of physic nut (Jatropha curcas) is the function of planting material, growing condition, and alsocanopy architecture maintenance. The objective of the research was to determine the effect of pruning time on yield of physicnut. An experiment was conducted from November 2007 to November 2010 in North Lombok, West Nusa Tenggara using WestLombok genotype. The experimental design was randomized block design with three replications. There were four treatmentsi.e. a) without pruning, b) pruning at planting time, c) pruning of 1-year old trees at dormance period (after harvesting), andd) pruning of 2-years old trees at dormancy period (after harvesting). Results showed that development and maintenance ofphysic nut canopy is one of important agronomic practices to obtain high seed production. The best time for pruning during3-years production cycle was at the end of harvest of 1-year old trees which could yield more than 4 tonnes seed ha-1 .